2020
DOI: 10.14786/flr.v8i6.663
|View full text |Cite
|
Sign up to set email alerts
|

Regulating distance to the screen while engaging in difficult tasks

Abstract: Regulation of distance to the screen (i.e., head-to-screen distance, fluctuation of head-to-screen distance) has been proved to reflect the cognitive engagement of the reader. However, it is still not clear (a) whether regulation of distance to the screen can be a potential parameter to infer high cognitive load and (b) whether it can predict the upcoming answer accuracy. Configuring tablets or other learning devices in a way that distance to the screen can be analyzed by the learning software is in close reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…By analyzed eye movements, educators can better understand how students interact with the platform, leading to improvements in design and instructional strategies (Erdogan et al 2023). Zhao et al (2014) investigated differences in reading strategies using eye-tracking. They focused on the quantitative analysis of fixations, the number of visits to individual AOIs, time to first fixation, and transitions between images and text.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzed eye movements, educators can better understand how students interact with the platform, leading to improvements in design and instructional strategies (Erdogan et al 2023). Zhao et al (2014) investigated differences in reading strategies using eye-tracking. They focused on the quantitative analysis of fixations, the number of visits to individual AOIs, time to first fixation, and transitions between images and text.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in previous research, the group who was shown animated images received a higher amount of information and spent more time on a task than the group who was shown static pictures [56]. There is also evidence from eye‐movement patterns showing that participants spent much more time working on tasks with difficult questions than with easy questions [57]. Participants spent much more time‐solving tasks when they encountered difficulties (incorrect answers) compared with when they did not (correct answers) [58].…”
Section: General Methodsmentioning
confidence: 99%